648 Cytokine changes during immune-related adverse events and steroid treatment in melanoma patients receiving immune checkpoint inhibitors. (9th November 2020) - Tyan, Kevin; Baginska, Joanna; Brainard, Martha; Giobbie-Hurder, Anita; Severgnini, Mariano; Manos, Michael; Haq, Rizwan; Buchbinder, Elizabeth; Ott, Patrick; Stephen Hodi, F; Rahma, Osama
Abstract : Background: Immune checkpoint inhibitors (ICIs) often lead to immune-related adverse events (irAEs) with effects ranging from treatment interruption to mortality. 1 2 Most irAEs are treated with corticosteroids despite mounting evidence to suggest that corticosteroid treatment may blunt antitumor efficacy. 3–5 There is a paucity of data on biomarkers that predict irAEs or characterize inflammatory changes during irAEs or steroid use. We sought to identify changes in cytokines that correlate with irAEs and may suggest inflammatory mechanisms that enable rational therapies. We also aimed to study the impact of steroid treatment on cytokine levels to better understand their immunomodulatory effect. Methods: We analyzed longitudinal levels of 34 cytokines in 52 melanoma patients receiving ICIs who developed irAEs. Luminex assay was performed on serum at baseline, 1, 2, and 3 months after starting ICI. Baseline cytokine levels were compared with incidence and grade of irAEs. Cytokine fold-change was compared between patients who did not develop irAEs, patients who developed irAEs without receiving steroids, and patients who developed irAEs who received steroids during the longitudinal profiling period. Results: 33/52 (63.5%) patients were male and median age was 70.5 years. 47 patients (90.4%) received anti-PD1 monotherapy, 4 patients (7.7%) received anti-CTLA-4 monotherapy and one patient received combination therapy (1.9%). Twenty-eight patients (53.8%) developed grade 1–2 irAEs and 24 patients (46.2%) developed grade 3-4 irAEs. There were no differences in cytokine levels between patients with grade 1-2 vs. grade 3-4 irAEs. Patients with dermatitis (N = 8) had significantly higher baseline Ang-1 (p = 0.006) and CD40L (p = 0.005, figure 1 A). Patients with pneumonitis (N = 4) had significantly higher baseline IL-17 (p = 0.009, figure 1 B). There was a trend towards lower GCSF levels in patients developing colitis (N = 8, p = 0.08, figure 1 C). We observed a harmonization of cytokine fold-change in patients who developed irAEs without receiving steroids: 269/276 (97.5%) of pairwise comparisons exhibited fold-change in the same upwards or downwards direction (figure 2 ). In contrast, corticosteroid treatment in patients with irAEs appeared to alter cytokine fold-change to a discordant pattern (214/276, 77.5%) mirroring patients who did not develop irAEs during the longitudinal profiling period (213/276, 77.2%). Example patient timelines are shown in figure 3 . Conclusions: Baseline cytokine levels correlate with specific irAEs in melanoma patients receiving ICIs. irAEs appear to drive a concordant pattern of cytokine fold-change, which is disrupted by corticosteroid administration. These findings should be validated in larger cohorts. Ethics Approval: Patients were identified from DFCI's melanoma bio-specimen banking protocol (DFCI protocol 05-042) References: Rahma OE, Ott PA. General Principles of Immune-Related Toxicities. In: Enrstoff M, Puzanov I, Robert C, Diab A, Hersey P, ed. SITC's Guide to Managing Immunotherapy Toxicity. Society for Immunotherapy of Cancer; 2018: Chapter 5. Hodi FS, O'Day SJ, McDermott DF, et al. Improved survival with ipilimumab in patients with metastatic melanoma. N Engl J Med 2010;363 :711–723. Faje AT, Lawrence D, Flaherty K, et al. High-dose glucocorticoids for the treatment of ipilimumab-induced hypophysitis is associated with reduced survival in patients with melanoma. Cancer 2018;124(18):3706–3714. Arbour KC, Mezquita L, Long N, et al. Impact of baseline steroids on efficacy of programmed cell death-1 and programmed death-ligand 1 blockade in patients with non-small-cell lung cancer. J Clin Oncol 2018;36(28):2872–2878. Libert C, Dejager L. How Steroids Steer T Cells. Cell Reports 2014;7(4):938–939.